Influence of Body Mass Index, Waist Circumference, and Physical Activity on Age of Menarche in Female Adolescent - Rachma, Ulfa Puspita; Moelyo, Annang Giri; Aryani, Imasari (Journal of Maternal and Child Health, 2021)
Background: The age of menarche which was referred to first time of teenagers had menstruation can be affected by anthropometric index, including body mass index, and waist circumference. Differences in measurement of body mass index, waist circumference, and intensity of physical activity will make some differences in age of menarche. This research aimed to determine the influence of body mass index, waist circumference and physical activity with age of menarche in late adolescent girls in Surakarta. Subjects and Method: The data collected by observed 359 adolescent girls aged 15 until 18 years old in Surakarta during September to October 2016 using observational analytic with cross sectional methods. The independent variables were body mass index, waist circumference, and physical activity. The dependent variable is age of menarche. Body mass index is measured using BW (kg)/BH² (m²) formula, in which: BW is Body Weight (measured using digital standardized scales) and BH is Body Height (measured using standardized microtoise). Students asked to fill in the questionnaire that contain questions regarding reproductive health especially menarche and physical activity questionnaire (IPAQ). The data is processed using SPSS for Windows 23.0 and are analyzed using multiple regression analysis. Results: From the 359 respondents, the mean of age of menarche is 12.6 years (Mean= 12.6; SD= 1). Mean of body mass index is 21.42 kg/m² (Mean= 21.42; SD= 4.44). Mean of waist circumference is 70.41 cm (Mean= 70.41; SD= 7.47). There are 87 respondents (24.2%) with low physical activity, 100 respondents (29.5%) with moderate physical activity, and 166 respondents (46.2%) with high physical activity. Physical activity has significant influence positively (OR= 1.98; 95% CI= 0.39 to 4.72; p= 0.017) on the age of menarche. Conclusion: Physical activity has significant influence on the age of menarche in adolescent girls in Kota Surakarta, Indonesia.